THE INFLUENCE OF LIFESTYLE AND BRAND IMAGE ON CUSTOMER PURCHASE INTENTION AT STARBUCKS IN NORTH SULAWESI - Komaling, Cindy; Mangantar, Maryam; Tielung, Maria (Universitas Sam Ratulangi, 2026)
This study aims to examine the influence of lifestyle and brand image on customer purchase intention at Starbucks in North Sulawesi. The research employs a quantitative approach using primary data collected through questionnaires distributed to Starbucks consumers in Manado and Bitung. The sample consists of 100 respondents selected using purposive sampling. Data analysis techniques include validity and reliability tests, classical assumption tests, multiple linear regression analysis, F-test, and t-test using SPSS. The results indicate that lifestyle and brand image have a positive and significant effect on customer purchase intention, both partially and simultaneously. These findings suggest that aligning brand positioning with consumer lifestyle and maintaining a strong brand image are essential strategies to enhance customer purchase intention in the coffee shop industry. Keywords: Lifestyle, Brand Image, Customer Purchase Intention